2012
DOI: 10.4236/ijcm.2012.32024
|View full text |Cite
|
Sign up to set email alerts
|

Intralesion and Curaderm<sup>BEC5</sup> Topical Combination Therapies of Solasodine Rhamnosyl Glycosides Derived from the Eggplant or Devil’s Apple Result in Rapid Removal of Large Skin Cancers. Methods of Treatment Compared

Abstract: Solasodine rhamnosyl glycosides (SRGs) are chemotherapeutic agents for the treatment of cancer. SRGs in a cream formulation, Curaderm BEC5 , is very effective for the treatment of nonmelanoma skin cancers with excellent cosmetic end results. Intralesion injection of SRGs successfully dispose of very large tumours in animals without any clinical adverse effects. The mode of action of SRGs is by apoptosis. In this study, it is shown that small to large basal cell carcinomas are effectively treated only with topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Further clinical studies showed that Curaderm BEC5 eliminated basal cell carcinoma in areas that were difficult to treat by any modality [46]. Very large basal cell carcinomas were shown to be successfully treatable with Curaderm BEC5 [40,47].…”
Section: Basal Cell Carcinomamentioning
confidence: 99%
“…Further clinical studies showed that Curaderm BEC5 eliminated basal cell carcinoma in areas that were difficult to treat by any modality [46]. Very large basal cell carcinomas were shown to be successfully treatable with Curaderm BEC5 [40,47].…”
Section: Basal Cell Carcinomamentioning
confidence: 99%
“…The glycoalkaloids solamargine and solasonine singly or in combination are known to be good antineoplastic biological therapeutic agents . These chemical compounds occur in plants of the Solanaceae family such as S. linnaeanum (devil's apple) and S. melongena (egg-plant) [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The solasodine glycosides enhance the intrinsic ratio of Bax to Bcl-2 by up-regulating Bax and down-regulating Bcl-2 and Bcl-xL expressions. These effects result in activation of Caspase −8, −9 and −3 in cancer cells, indicating that extrinsic and intrinsic apoptotic pathways in cancer cells [8,22,23,[27][28][29][30][31]38,39] are triggered by the solasodine glycosides.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations